2020
DOI: 10.1039/c9fo02975c
|View full text |Cite
|
Sign up to set email alerts
|

Bok-choy promotes growth performance, lipid metabolism and related gene expression in Syrian golden hamsters fed with a high-fat diet

Abstract: This study aims to investigate the beneficial effects of two cultivars of bok-choy, ‘Suzhouqing’ (green cultivar) and ‘Ziluolan’ (purple cultivar), on growth performance, lipid metabolism and related gene expressions in Syrian golden hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Oryzanol is an attractive candidate because of its strong protective effect against metabolic syndrome and its noncytotoxic effect on experimental rodent models. , The results from our studies confirm that oryzanol supplementation significantly attenuated HFCD-induced metabolism disorder, including decreased fat accumulation, serum lipid accumulation, and blood glucose. Other studies report that HFCD led to body fat accumulation and cholesterol metabolism disorder in rodents. , In this study, HFCD treatment increased body weight, fat tissue weight, and serum LDL-c and TG levels, and the LDL-c/HDL-c ratio, all consistent with related studies. , In our previous study, serum LDL-c level of the mice group that received orally administrated oryzanol was reduced by 30% compared to that of the high-fat-diet fed mice group; serum TG levels also decreased significantly in the oryzanol group . Wang et al reported an antihyperlipidemic effect of oryzanol and that the LDL-c/HDL-c ratio decreased by about 22% compared to the ratio in the hyperlipidemia model group .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Oryzanol is an attractive candidate because of its strong protective effect against metabolic syndrome and its noncytotoxic effect on experimental rodent models. , The results from our studies confirm that oryzanol supplementation significantly attenuated HFCD-induced metabolism disorder, including decreased fat accumulation, serum lipid accumulation, and blood glucose. Other studies report that HFCD led to body fat accumulation and cholesterol metabolism disorder in rodents. , In this study, HFCD treatment increased body weight, fat tissue weight, and serum LDL-c and TG levels, and the LDL-c/HDL-c ratio, all consistent with related studies. , In our previous study, serum LDL-c level of the mice group that received orally administrated oryzanol was reduced by 30% compared to that of the high-fat-diet fed mice group; serum TG levels also decreased significantly in the oryzanol group . Wang et al reported an antihyperlipidemic effect of oryzanol and that the LDL-c/HDL-c ratio decreased by about 22% compared to the ratio in the hyperlipidemia model group .…”
Section: Discussionsupporting
confidence: 91%
“…7,27 In this study, HFCD treatment increased body weight, fat tissue weight, and serum LDL-c and TG levels, and the LDL-c/HDL-c ratio, all consistent with related studies. 28,29 In our previous study, serum LDL-c level of the mice group that received orally administrated oryzanol was reduced by 30% compared to that of the high-fat-diet fed mice group; serum TG levels also decreased significantly in the oryzanol group. 21 Wang et al reported an antihyperlipidemic effect of oryzanol and that the LDL-c/HDL-c ratio decreased by about 22% compared to the ratio in the hyperlipidemia model group.…”
Section: ■ Discussionmentioning
confidence: 90%
“…The decreased level of LPL blocks the lipid metabolism and helps the accumulation of fat in the liver ( 38 ). Several studies showed the increasing levels of FASN and CEBP- α in the high-fat diet compared with the control group ( 39 , 40 ). The reduced level of HMG-CoA participates in the reduction of cholesterol synthesis, which is associated with lipid metabolism, whereas PPAR- α and CPT2 genes are associated with fatty acid β-oxidation ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that we have established a well-high lipid model in Golden Syrian hamsters. We don’t use negative control instead of using self-control when feeding with HFD because there were several reports claiming that more than 1.3-fold changes in serum TC, TG, and LDL are enough to establish a well-high lipid model [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%